A Case Study on Souq.com - Othman Ahmad; Abhishek Rajawat; Lamia Alkandri; Fawaz Al Enezi (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
Souq.com is the largest e-commerce website in the Arab world with more than 400,000 products ranging from electronics, fashion,household ,watches,perfumes,and more. Today,it attracts more than 23 million visitors a month ,and is growing rapidly because of the increasing number of online shoppers in the Arab world. Often referred to as â€œAmazon Middle Eastâ€, it operates as a retail location and serves a market for third party vendors. It offers a convenient and secure shopping experience with online payment, cash on receipt and free return. Established in 2005, it was a pioneer in online shopping in the region as an auction site and linked to the Arab Internet portal Maktoob. When Yahoo acquired Maktoob in August 2009, it was not included in the deal, separated from Maktoob to remain part of Jabbar Internet Group. Then, in early 2011, the site became a market model selling at fixed prices, and then the retail division was launched in late 2011. In addition to its headquarters in Dubai, UAE, it meets local market needs with commercial offices in Egypt, Saudi Arabia and Kuwait; and a technical development center in Jordan and India.